THE COURSE AND PATHOMORPHOLOGICAL DIAGNOSIS OF MIXED INFECTIONS (SALMONELLA-COLIBACTERIOSIS) IN RABBITS - Intizor Sultanova; Olimjon Dzhuraev; Alisher Khushnazarov (Ecominds Press, 2025)
The article covers information about pathological processes during the mixed development of salmonellosis and colibacillosis in rabbits. The clinical signs and course of this mix of infection in rabbits subjected to artificial infection with Escherichia and Salmonella at a dose of 1.5 billion (0.75 billion each) of microbial bodies of pathogens are presented in detail. The results of pathological and histological studies of internal organs in experimental animals are widely described.